Pemberdayaan Kelompok Kerja Guru (KKG) Pada Gugus Hasanudin Di Kecamatan Karangrayung Kabupaten Grobogan - Sutrisno, Agus; , Prof. Dr. Bambang Sumardjoko; , Dr. Sabar Narimo, M.M., M.Pd (2016)
This study have three aims to describes: 1) empowerment of learning administration in teacher working community, 2) empowerment of the making of instructional media in teacher working community, 3) empowerment of learning implementation in teacher working community at Cluster Hasanudin. This research is qualitative research with case study design. Data was collected by observation, interview, and documentation. Data analysis use interactive model of analysis. Results of this research there are three things about: 1) empowerment of learning administration in teacher working community at cluster Hasanudin done by to communicate and consult on issues of student learning and the sharing information and experiences related to student learning. 2) Empowerment the making of instructional media in teacher working community resolved through several discussions and meetings. Activities related to the management of learning resources, learning materials procurement, development / production of learning materials, service learning materials, training and development of instructional media. 3) Empowerment of learning implementation in teacher working community at Cluster Hasanudin because of principals support, such as providing the opportunity for teachers to follow Teacher Working Community activities, convenience to teachers (provide an assignment letter required) to implement the Teacher Working Community activities, open ourselves to receive input results Teacher Working Community of the teacher as the improvement of learning quality, give permission to use the school facilities in practice Teacher Working Community activities to teachers participated indirectly in conveying the problems of teaching and learning activities for teachers to be discussed at the Teacher Working Community forum.